The Egidio Feruglio's collection in the Museum of Geology and Palaeontology of the University of Padova: its importance to the knowledge of Cenozoic mammals from South America - Vera, Bárbara Soledad (2015)
The Museum of Geology and Palaeontology of the University of Padova, Italy, houses an important and practically unknown collection of fossil mammals from Patagonia, southern Argentina. It consists of thousands of remains collected by the Italian geologist Egidio Feruglio in the 1920s and 1930s, during his fieldworks in Patagonia for the Dirección de Yacimientos Petrolíferos Fiscales. In this work, we disclose the history of this particular collection providing a list of the most important fossil mammals represented, including holotypes, and emphasizing its importance on palaeontological and stratigraphic issues of southern South America. Furthermore, the MGP-PD houses fossils and casts of South American mammals provided by Argentinean researchers, such as a very small collection probably donated by the Argentinean naturalist Prof. Florentino Ameghino, and several casts donated by Dr. Alberto Castellanos.